(untitled) (REMUNOM, 2025)
Introduction: Aging brings physiological changes such as loss of muscle and bone mass, endocrine changes and impairment of the vestibular system, which can maximize the occurrence of adverse events, such as falls, a public health problem associated with high rates of hospitalization and mortality in the elderly. Hydrotherapy can be used to take advantage of the physical properties of water as a strategy to improve functionality, by reducing joint stress, relieving pain, strengthening muscles, improving motor mobility, in addition to promoting relaxation and confidence, and is widely indicated for this population. Objective: to investigate the effects described in the current literature about Hydrotherapy in functional rehabilitation and prevention of falls in the elderly. Methodology: it was based on integrative research where ten articles were analyzed, between the years 2014 and 2024, based on experimental studies with the elderly. Results: indicate that the interventions improved balance, functional mobility, and muscle strength, contributing to the prevention of falls. Conclusion: Based on the analysis of current literature, hydrotherapy is an intervention capable of promoting functional rehabilitation and preventing the risk of falls in the elderly. It is an approach that favors independence and improves quality of life, promoting more active and healthy aging. Keywords: Hydrotherapy, Postural balance, Functionality, Elderly, Falls